Engineered neutrophil-derived exosome-like vesicles for targeted cancer therapy - Zhang Jiahui; Ji Cheng; Zhang Hongbo; Shi Hui; Mao Fei; Qian Hui; Xu Wenrong; Wang Dongqing; Pan Jianming; Fang Xinjian; Santos Helder A.; Zhang Xu (AMER ASSOC ADVANCEMENT SCIENCE, 2022)
Neutrophils are the most abundant innate immune cells in human circulation; however, their derived exosomes have been rarely studied for tumor treatment. Here, we reported that exosomes from neutrophils (N-Ex) induce tumor cell apoptosis by delivering cytotoxic proteins and activating caspase signaling pathway. In addition, we decorated N-Ex with superparamagnetic iron oxide nanoparticles ( SPIONs) to achieve higher tumor-targeting therapeutic effect. We further fabricated exosome-like nanovesicles from neutrophils (NNVs) at high yield. Compared with liposome-loaded doxorubicin (DOX) and natural NNVs, DOX-loaded NNVs show an improved inhibition of tumor cell proliferation. Moreover, DOX-loaded, SPION-decorated NNVs selectively accumulate at the tumor sites under an external magnetic field, effectively restraining tumor growth and extensively prolonging the survival rate in mice. Overall, a simple and effective method to engineer N-Ex and NNVs at clinical applicable scale was developed, which enables the efficient and safe drug delivery for targeted and combined tumor therapy.